Histological Study of Induced Incisions on Rabbits’ Tongues with Three Diode Lasers with Different Wavelengths in Continuous Mode - Salwa Yammine; Edgard Jabbour; Sami El Toum; Antoine Cassia (Scientifica)
Objective. Diode lasers have multiple indications in everyday dental practice. They allow carrying out incisions, coagulation of soft tissue, and Low-Level Laser Therapy. The goal of this study is to compare histologically the tissue interaction zones and edges of an induced laser incision on rabbits’ tongues with three different wavelengths of 810, 940, and 980 nm in continuous mode. Methods. Fourteen male rabbits were divided into six groups. Each animal underwent three incisions of 10 mm length on the right ventral face of the tongue, carried out in continuous mode with three diode lasers with different wavelengths of 810, 940, and 980 nm. Rabbits were sacrificed at 0, 1, 2, 6, and 15 hours and 14 days. Five rabbits were sacrificed at 0 hours and 2 hours and one rabbit was sacrificed at 1, 6, and 15 hours and at 14 days. The appearance of neutrophils marked the onset time of the inflammatory reaction. Histological study of the incisions was chosen to evaluate the edges and to measure the depth and width of carbonization and necrotic and inflammatory zones. Healing was evaluated at 14 days. Friedman test was used to assess statistical differences between groups. Results. In the experimental adopted conditions, the carbonization zone was marked by degradation of vacuoles and an elongation of nuclei and was observed on the edges of incisions. Carbonization and necrotic and inflammatory zones were measured for rabbits sacrificed at 0, 1, 2, 6, and 15 hours but the onset of inflammation zone marked by the infiltration of neutrophils did not appear before 6 hours. The neutrophils infiltration was higher at 15 hours than at 6 hours. Complete healing was shown at 14 days. According to the time for the regularity of the edges, the interpretation was qualitative without a statistical test. The statistical analysis of the three different diode lasers in this study showed nonsignificant difference between the different groups for the depth (p=0.121) and width (p=0.376) of the incisions, the carbonization zone (p=0.692), and the necrotic zone (p=0.223). For the inflammation zone at 6 and 15 hours, statistical analysis was not carried out; only one rabbit was enough to evaluate onset of neutrophils infiltration and to compare its density for 6 and 15 hours. Conclusion. These results indicate that diode laser used in the continuous mode is predictable for induced incision. The use of three diode lasers with different wavelengths of 810, 940, and 980 nm did not reveal a significant statistical difference according to depth and width of the incision and for carbonization and necrotic zone. The appearance of neutrophils was marked between 4 and 6 hours and was higher at 15 hours.